Treatment choices for patients with invasive lobular breast cancer: a doctor survey. Issue 4 (9th June 2015) - Jacobs, Carmel; Ibrahim, Mohamed F.K.; Clemons, Mark; Hutton, Brian; Simos, Demetrios; Caudrelier, Jean‐Michel; Graham, Ian D.; Smith, Stephanie; Addison, Christina; Arnaout, Angel
Abstract Rationale, aims and objectives Invasive lobular breast cancer (ILC) has distinct features that present challenges for management. We surveyed doctors regarding management approaches, opinions on quality of evidence supporting their practice, and future research needs. Methods An online questionnaire was developed and circulated to breast cancer surgical, radiation and medical oncologists. Results The questionnaire was completed by 88/428 doctors (20.6%); 22/56 (39.3%) surgeons, 21/64 (32.8%) radiation oncologists and 45/308 (14.6%) medical oncologists. The majority (65%) of surgeons were comfortable treating ILC patients using the same surgical management as patients with invasive ductal cancers (IDC). Furthermore, 25% would perform a similar surgery but would obtain larger gross margins. There was equipoise for radiation oncologists regarding whether or not ILC was an independent risk factor for local‐regional recurrence after either breast‐conserving surgery or mastectomy. Of those radiation oncologists who believe ILC is an independent risk factor for recurrence after mastectomy, 44.4% would offer radiation in the absence of usual indications. Medical oncologists approached systemic therapy for ILC patients similarly to those with comparable IDCs. Areas identified as most controversial and requiring future research were preoperative magnetic resonance imaging, radiotherapy post‐mastectomy and the responsiveness of ILC to adjuvant chemotherapy compared with endocrine therapy. Conclusions There is a variation in doctors' beliefs, management and opinions regarding the quality of evidence for the management of ILC. Clinical trials specifically assessing the management of ILC are required to guide clinical practice.